PENGARUH MOTIVASI WISATA, PERSEPSI TENTANG DAYA TARIK DAN KUALITAS PELAYANAN TERHADAP LAMA TINGGAL WISATAWAN DI PROVINSI DIY - Nur Budhi Puji Wibowo (JURNAL NASIONAL PARIWISATA, 2012)
The aim of this research is to find out and analyze the influence of tourist motivation and perception of the destination attractiveness and tourism service quality to the tourist’s length of stay in Yogyakarta Special Province. As one of the most outstanding tourism destination in Indonesia, this province is visited by over than one million domestic and foreign visitors every year. Visitor’s length of stay as one of the important indicators of tourism development success plays significant role to maximize the economical benefits in order to increase prosperity for the local community. Therefore, this research means very important to understand the influence’s significances of each independent variables both in single and aggregate to the tourist’s length of stay in Yogyakarta Special Province.The research result shows that variable of tourist motivation has a positive and signifi-cant influence for the domestic tourist’s length of stay in Yogyakarta Special Province. However, for the foreign tourists it has no significant influence for their length of stay. The variable of perception of the destination attractiveness has no significant influence for the domestic tourist’s length of stay in Yogyakarta Special Province. In the other hand, it has a positive and significant influence for the foreign tourist’s length of stay. Afterward, the variable of perception of the tourism service quality has no significant influence for the domestic tourist’s length of stay in Yogyakarta Special Province. In the other side, it has a positive and significant influence for the foreign tourist’s length of stay. In aggre-gate, the variable of tourist’s motivation and perception of the destination attractiveness and tourism service quality have a positive and significant influence for the tourist’s length of stay in Yogyakarta Special Province both for domestic and foreign tourist. The values of determination coefficients for each tourist group are 26,1% and 16,1%.